IMPLEMENTASI KEBIJAKAN PERATURAN BUPATI SIDOARJO NOMOR 107 TAHUN 2018 DALAM PENGAWASAN PENDIRIAN BANGUNAN - Dwiki Dimas Dwiki Prakoso; Muchammad Wahyono; Anggraeny Puspaningtyas (PRAJA observer: Jurnal Penelitian Administrasi Publik (e- ISSN: 2797-0469))
The problem in Sidoarjo Regency is that there are still many buildings that do not have an IMB, one of which is residential buildings. The purpose of this study was to determine and analyze the implementation of building construction supervision and the supporting and inhibiting factors in supervising the construction of buildings. In this study, the method used is a qualitative research type with a descriptive approach. Data obtained by researchers through interviews, observation, and documentation. In this study using the analysis technique of the Miles, Huberman and Saldana model. Based on the results of the research that has been done, the implementation of establishment supervision requires a solution to solve the problem so that the building is still not optimal in carrying out its implementation, so that there are still residential buildings that are still not monitored. The conclusion of this researcher is that the implementation of the policy for supervising the construction of buildings is not yet optimal because there are still existing problems. Thus, the implementation of the policy for supervising the construction of buildings has not been in accordance with the goals and objectives that have been set.